BASLAWÍSH KLASSLARDA SABAQ PROCESINDE INTERAKTIV METODLARDAN PAYDALANÍW IMKANIYATLARÍ - Abdalieva, P.I. (SCIENCE and SOCIETY, 2024)
This article discusses some features of using of interactive methods in the learning process in primary grades.